THE BENEFICIAL VALUES OF APPLYING PEER ASSESSMENT STRATEGY IN MODERN EFL WRITING LEARNING ENTERPRISES - Kristian Florensio Wijaya (Magister Scientiae, 2024)
Comprehensive attainment of fruitful second language writing learning outcomes undeniably hinges on the meaningful usage of assessments. In the light of appropriate, contextual, and purposeful assessments, EFL learners can potentially endure better-facilitated writing learning enterprises as they fully locate their particular writing weaknesses to be further amended in the future. Peer assessment plays a pivotal role in response to this main nature of writing assessment purposes in which EFL learners significantly broaden their current writing perspectives, knowledge, skills, and experiences in concord with varied constructive suggestions derived from entrusted learning companions. This small-scale library study was initiated with the employment of thematic analysis to generate more comprehensible, reliable, and relatable research results. To that end, the researcher thematically analyzed the previously related research findings from 25 published peer-assessment journal articles both nationally and internationally wide. The thematically categorized research results suggested second language educators start reinforcing their learners’ writing proficiency skills growth with the internalization of a peer assessment strategy by which they progressively transform into more passionate and autonomous writers.